ExplanationThe sum of Mason and Gunther’s ages 4 years from now requires adding 4 to both ages.

The question asks for the following, the sum of Mason and Gunther’s ages 4 years from now:

\((M + 4) + (G + 4) = ?\)

\(M + G + 8 = ?\)

Since Mason is twice as old as Gunther was 10 years ago, put (G – 10) in parentheses and build the second equation from there (the parentheses are crucial):

\(M = 2(G - 10)\)

\(M = 2G - 20\)

Note that the answer choices ask for the sum of the ages 4 years from now, in terms of G, so substitute for M (the variable you substitute for is the one that drops out).

Substituting from the second equation into the first:

\((2G - 20) + G + 8 = ?\)

3G - 12 = ?

This matches choice C.Alternatively, you could write the second equation, M = 2(G – 10), and then come up with two values that “work” in this equation for M and G. The easiest way to do this is to make up G, which will then tell you M. For instance, set G = 12 (use any number you want, as long as it’s over 10, since the

problem strongly implies that Gunther has been alive for more than 10 years):

\(M = 2(12 - 10)\)

\(M = 4\)

If Gunther is 12, then Mason is 4. In four years, they will be 16 and 8, respectively. Add these together to get 24.

Now, plug G = 12 into each answer choice to see which yields the correct answer (for this example), 24. Only choice (C) works.

_________________

Sandy

If you found this post useful, please let me know by pressing the Kudos Button

Try our free Online GRE Test